2014
DOI: 10.1055/s-0034-1365811
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic flushing with pronase improves the quantity and quality of gastric biopsy: a prospective study

Abstract: Endoscopic flushing with pronase not only improved the depth of biopsy but also the anatomical orientation and overall diagnostic adequacy. Pronase can be recommended for flushing during EGD to improve the quantity and quality of biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Detecting these premalignant tissues is important in planning surveillance for such patients in detecting early gastric cancer. Similar finding was noted by SY Lee et al ., who used a flushing technique for the application of Pronase that facilitated improvement in depth of the biopsy, anatomical orientation and overall diagnostic adequacy. More findings of atrophic gastritis and intestinal metaplasia are also very important because they are associated with early gastric cancer .…”
Section: Discussionsupporting
confidence: 84%
“…Detecting these premalignant tissues is important in planning surveillance for such patients in detecting early gastric cancer. Similar finding was noted by SY Lee et al ., who used a flushing technique for the application of Pronase that facilitated improvement in depth of the biopsy, anatomical orientation and overall diagnostic adequacy. More findings of atrophic gastritis and intestinal metaplasia are also very important because they are associated with early gastric cancer .…”
Section: Discussionsupporting
confidence: 84%
“…To improve the accuracy of biopsy, a previous study used pronase to wash the mucosal surface of the lesions, which increased the depth of the biopsy, facilitated accurate positioning, and helped improve the accuracy of the biopsy. 18 In addition, Jiang et al 19 have shown that a targeted biopsy with ME-NBI could achieve a high pathological positive rate with a small quantity of tissues. However, targeted biopsy with ME-NBI increases the difficulty of the biopsy procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, gastric mucus reduced capsule navigability in three patients. Removal of mucus by drugs such as simethicone [15] and pronase [16] has been shown to alleviate the problem, but their use requires fur- ther investigation. An air-water interface is required for navigation of the capsule within the stomach, and most patients tolerated ingestion of the large amount of water.…”
mentioning
confidence: 99%